Impact of COVID 19 on CAREC aviation and tourism. - Asian Development Bank (Manila,Philippines Asian Development Bank, [2021])
COVID-19 has had a devastating impact on global aviation as nearly all air travel came to a halt in late March and April 2020. In Central Asia, virtually all domestic and international air travel were suspended in an attempt to contain the spread of COVID-19. This crisis provides an opportunity to reset the aviation industry in CAREC countries through reforms, new strategies, and restructurings. The study takes into consideration the gravity of the situation in the region and offers some recommendations for dealing with and beyond the crisis.
Keywords: Industry and state -- Central Asia; Central Asia -- Economic integration; Electronic book